A phylogenetic re-evaluation of Phyllosticta (botryosphaeriales) - S. Wikee (2018)
Phyllosticta is a geographically widespread genus of plant pathogenic fungi with a diverse host range. This study redefines Phyllosticta, and shows that it clusters sister to the Botryosphaeriaceae (Botryosphaeriales, Dothideomycetes), for which the older family name Phyllostictaceae is resurrected. In moving to a unit nomenclature for fungi, the generic name Phyllosticta was chosen over Guignardia in previous studies, an approach that we support here. We use a multigene DNA dataset of the ITS, LSU, ACT, TEF and GPDH gene regions to investigate 129 isolates of Phyllosticta, representing about 170 species names, many of which are shown to be synonyms of the ubiquitous endophyte P. capitalensis. Based on the data generated here, 12 new species are introduced, while epitype and neotype specimens are designated for a further seven species. One species of interest is P. citrimaxima associated with tan spot of Citrus maxima fruit in Thailand, which adds a fifth species to the citrus black spot complex. Previous morphological studies lumped many taxa under single names that represent complexes. In spite of this Phyllosticta is a species-rich genus, and many of these taxa need to be recollected in order to resolve their phylogeny and taxonomy. © CBS-KNAW Fungal Biodiversity Centre.